Central Bank Digital Currency: A New Instrument of Monetary Policy - Kóczián, Balázs; Kollarik, András; Kiss, Lóránt; Simon, Péter (Public Finance Quarterly, 2022)
Central bank digital currency is a claim on the central bank, which is accessible by a wide range of customers, digital, flexible and potentially interest-bearing. The new asset is being researched in many countries, and widening the accessibility of financial services, creating the digitalized form of cash with monetary policy considerations being among its motivations. An interest-bearing central bank digital currency could make the central bank’s monetary transmission direct, which could improve the efficiency of monetary policy. Furthermore, the asset could help to strengthen competition among banks and could support the spread of financial innovations. Risks related to the instrument, such as disintermediation, can be counterbalanced by the increasing deposit volumes due to higher interest rates after the introduction of the instrument, and by limits set on the maximum holdings of the asset. An interest-bearing central bank digital currency can make targeted monetary policy possible, furthermore, the direct transmission of interest rates could enhance the efficiency of monetary transmission.